Changes in auditory perceptions and cortex resulting from hearing recovery after extended congenital unilateral hearing loss - Firszt, Jill B.; Reeder, Ruth M.; Holden, Timothy A.; Burton, Harold; Chole, Richard A. (Frontiers in Systems Neuroscience, 2013)
Monaural hearing induces auditory system reorganization. Imbalanced input also degrades time-intensity cues for sound localization and signal segregation for listening in noise. While there have been studies of bilateral auditory deprivation and later hearing restoration (e.g. cochlear implants), less is known about unilateral auditory deprivation and subsequent hearing improvement. We investigated effects of long-term congenital unilateral hearing loss on localization, speech understanding, and cortical organization following hearing recovery. Hearing in the congenitally affected ear of a 41 year old female improved significantly after stapedotomy and reconstruction. Pre-operative hearing threshold levels showed unilateral, mixed, moderately-severe to profound hearing loss. The contralateral ear had hearing threshold levels within normal limits. Testing was completed prior to, and three and nine months after surgery. Measurements were of sound localization with intensity-roved stimuli and speech recognition in various noise conditions. We also evoked magnetic resonance signals with monaural stimulation to the unaffected ear. Activation magnitudes were determined in core, belt, and parabelt auditory cortex regions via an interrupted single event design. Hearing improvement following 40 years of congenital unilateral hearing loss resulted in substantially improved sound localization and speech recognition in noise. Auditory cortex also reorganized. Contralateral auditory cortex responses were increased after hearing recovery and the extent of activated cortex was bilateral, including a greater portion of the posterior superior temporal plane. Thus, prolonged predominant monaural stimulation did not prevent auditory system changes consequent to restored binaural hearing. Results support future research of unilateral auditory deprivation effects and plasticity, with consideration for length of deprivation, age at hearing correction, degree and type of hearing loss.